Overview of dominantly inherited AD and top‐line DIAN‐TU results of solanezumab and gantenerumab: Results of the DIAN‐TU prevention trial of solanezumab and gantenerumab in dominantly inherited AD. (7th December 2020) - Bateman, Randall J; Aschenbrenner, Andrew J.; Benzinger, Tammie L.S.; Clifford, David; Coalier, Kelley; Cruchaga, Carlos; Fagan, Anne M.; Farlow, Martin R.; Goate, Alison M.; Gordon, Brian A.; Hassenstab, Jason; Jack, Clifford R.; et al.
Abstract: Background: Alzheimer's disease (AD) prevention trials aim to intervene prior to significant neuronal loss, brain damage, and symptom onset to delay or slow cognitive decline. In dominantly inherited AD (DIAD), mutation carriers develop symptomatic AD at predictable ages with near 100% penetrance. In 2012, the Dominantly Inherited Alzheimer Network Trials Unit Adaptive Prevention Trial (DIAN‐TU APT) platform launched a double‐blind, randomized, placebo‐controlled, parallel group trial of two anti‐amyloid‐beta monoclonal antibodies with two different antigenic targets, gantenerumab and solanezumab (NCT01760005). The DIAN‐TU scientific development, implementation of the first AD prevention trial, trial challenges and opportunities, including dose escalation, and top‐line results will be presented. Method: DIAN was established in 2008 in response to a call from the National Institute of Aging to establish a network to study DIAD and enable future clinical trials. Successive breakthroughs in understanding disease processes enabled the launch of the DIAN‐TU adaptive prevention trial, a global adaptive platform trial supporting testing multiple drugs in parallel. The DIAN‐TU partners include patients and families at risk for DIAD, global academic researchers, the NIH, Alzheimer's Association, philanthropic supporters, the DIAN‐TU Pharma Consortium, and pharmaceutical companies with drugs being tested. Important milestones include developing a platform to enable a comprehensive efficient treatment trial for this rare population, adding tau PET as part of AMP AD, adapting dosing mid‐trial and extending the original biomarker trial to continue randomized dosing to test a cognitive endpoint until the last patient reaches 4 years, developing a disease progression statistical model and inclusion of DIAN observational data to increase the power to determine drug effects. Result: The primary and key secondary outcomes of the DIAN‐TU trial will be presented for each therapy in the context of targeting amyloid‐beta at pre‐clinical and clinically symptomatic stages of disease. Conclusion: These results inform about AD hypotheses, timing of treatment and the prospect of slowing, or preventing AD in DIAD and sporadic AD.